Geomorphology, morphodynamic, and surficial material of the Orosi Valley, Costa Rica - Cortés Granados, Víctor Manuel (2023)
Mangroves of the Tropical Northwestern Atlantic is a regional ecosystem subgroup (level 4 unit of the IUCN Global Ecosystem Typology). It includes the marine ecoregions of Bahamian, Carolinian, Eastern Caribbean, Floridian, Greater Antilles, Northern Gulf of Mexico, Southern Caribbean, Southern Gulf of Mexico, Southwestern Caribbean, Western Caribbean. The Tropical Northwestern Atlantic mangrove province mapped extent in 2020 was 17,408 km2 across, representing 11.8% of the global mangrove area. The diverse biota of this province is characterized by seven species of true mangroves, plus many associated taxa. Six species: Avicennia germinans, Laguncularia racemosa, Rhizophora mangle, Rizophora racemosa and Acrostichum aureum are categorized as Least Concern (LC) and Pelliciera rhizophorae as Vulnerable (VU) in the IUCN Red List of threatened species. Within the province, mangroves with lagoon carbonate and open coast carbonate typologies prevail. Despite sediment scarcity in carbonate regions, urban mangroves unexpectedly accumulate sediments and nutrients at faster rates, potentially enhancing resilience to rising sea levels. Threats to mangroves include deforestation due to various human activities, such as land use changes, agriculture, petroleum, tourism, and climate change-induced hurricanes. Anthropogenic impacts vary across countries. Sea level rise poses a multifaceted threat, from inundation and displacement of mangroves to elevated storm surge risks, necessitating comprehensive assessments and effective management for sustainability. The net area change of the mangrove in the Tropical Northwestern Atlantic has been -5.4% since 1996. If this trend continues an overall change of -13.1% is projected over the next 50 years. Furthermore, under a high sea level rise scenario (IPCC RCP8.5) ≈-75.9% of the Tropical Northwestern Atlantic mangroves would be submerged by 2060 with a relative severity within of ≥50% and <80%,. Moreover, 5.4% of the province’s mangrove ecosystem is undergoing degradation, with the potential to increase to 15.8% within a 50-year period, based on a vegetation index decay analysis. Overall, the Tropical Northwestern Atlantic mangrove ecosystem is assessed as Vulnerable (VU).